Significant Differences in Serum Creatinine and Potassium Levels Post-Hemodialysis: Perbedaan Signifikan Kadar Kreatinin Serum dan Kalium Setelah Hemodialisis - Yuliya Eka Putri; Puspitasari Puspitasari (Academia Open, 2023)
General Background chronic kidney disease (CKD) is a serious medical condition that results in a gradual decline in kidney function, requiring interventions such as hemodialysis to maintain patient health. Specific Background although there have been studies on changes in creatinine and potassium levels, there is a lack of understanding regarding the differences in these levels before and after hemodialysis procedures in CKD patients. Knowledge Gap previous research has not fully examined the impact of hemodialysis on creatinine and potassium levels comprehensively. Aims this study aims to explore the differences in serum creatinine and potassium levels in CKD patients undergoing hemodialysis. The results showed a significant difference in serum creatinine levels (p=0.001) and potassium levels (p=0.001) before and after hemodialysis. Novelty this study applied the Shapiro-Wilk method to test data normality and the Wilcoxon test for non-parametric analysis, which is relevant given the non-normal distribution of the data. Implications these findings have important implications for the management of CKD patients, highlighting the need for monitoring creatinine and potassium levels post-hemodialysis to improve clinical outcomes. Highlights: Significant reduction in serum creatinine levels post-hemodialysis (p=0.001). Notable decrease in serum potassium levels after treatment (p=0.001). Utilization of non-parametric tests for analyzing non-normally distributed data. Keywords: Chronic Kidney Disease, Hemodialysis, Serum Creatinine, Serum Potassium, Pretest-Posttest